Impact of Aging on Farmland Abandonment: Evidence from Rural China - Ziqi Zhang; Jingyi Ding; Kuan Zhang; Xin Deng (Land, 2025)
Reducing farmland abandonment is important to address food security issues. China is accelerating its transition into an aging society, and this change in the labor force structure may have an impact on farmland abandonment. This study is based on the China Labor Force Survey conducted in 2012, 2014, 2016, and 2018 and collects data from 29,704 valid farmer samples in 29 provinces and cities across the nation. We investigate how farmer aging affects farmland abandonment from the viewpoints of information, mutual aid, and factor substitution using the Tobit and mediation effect models. The core conclusions are as follows: (1) There is a significant positive correlation between aging and abandoned farmland, that is, the higher the degree of aging in rural households, the more likely it is that farmland will be abandoned and the larger the area of abandoned farmland. (2) Aging has a multi-level impact on abandoned farmland, that is, aging will aggravate the abandonment of farmland from the perspectives of household head characteristics, family characteristics, and village characteristics. (3) Using the mediation effect model, aging will increase the abandonment of farmland due to less use of the Internet, agricultural cooperatives, and mechanization. This conclusion provides a basis for policy intervention, indicating that improving agricultural digitalization and modernization and increasing policy subsidies may be an effective way to slow down land abandonment.